Editorial : Omics-driven crop improvement for stress tolerance. - Weicong, Qi; Jian, Chen; Yi, Han; Zhen, Li; Xiaofeng, Su; Freddy, Yeo Kuok San (Frontiers Media S.A., 2023)
Crop losses due to biotic and abiotic stresses are significant worldwide issues. According to a report of the Food and Agriculture Organization of the United Nations (FAO), an estimated 20-40% of global crop production is lost every year due to pests and diseases alone, while other environmental factors, like drought, floods, high salinity level in soil, and extreme temperatures contribute to the losses becoming even more severe. Crop yield stability and healthy growth under biotic and abiotic stresses have always been a major challenge for the plant/agricultural researchers. Crop resilience is an important trait, and it involves essential phenotypes that plant breeding researchers are concerned with. For instance, fusarium-head-blight resistance is highly desirable for breeding new wheat varieties nowadays. Therefore, improving stress tolerance becomes a major research direction in modern crop sciences